The Dynamics of Financial and Macroeconomic Determinants in Natural Gas and Crude Oil Markets: Evidence from Organization for Economic Cooperation and Development/Gulf Cooperation Council/Organization of the Petroleum Exporting Countries - Karacaer-Ulusoy, Merve; Kapusuzoglu, Ayhan (International Journal of Energy Economics and Policy, 2017)
This study analyzes the countries in the Organization for Economic Cooperation and Development (OECD), Gulf Cooperation Council (GCC) and Organization of the Petroleum Exporting Countries (OPEC) to test the casual relationship between world energy prices (Brent Oil, West Texas Intermediate (WTI), Dubai, Henry Hub (HH), Japan and Russia) and the liquidity level, stock market and industrial production. Augmented Dickey Fuller (ADF), Phillips-Perron (PP) and Kwiatkowski-Phillips-Schmidt-Shin (KPSS) unit root tests, Johansen cointegration and Granger causality analyses are implemented during the study. The empirical findings indicate that there are multidirectional relationships between the above-mentioned variables. These relationships can be explained by the factors that each country group owns within the framework of their energy sources, financial markets, economic conditions and geographical positions. The data accrued and analyzed in this study is presented as a contribution to guide policymakers, global investors and researchers in constituting an extensive country specific energy, macroeconomic and financial policies. Keywords: oil and natural gas prices, financial and economic developments, cointegration, causality JEL Classifications: C32, Q43